Plasma-grown graphene petals templating Ni–Co–Mn hydroxide nanoneedles for high-rate and long-cycle-life pseudocapacitive electrodes. Issue 45 (16th October 2015) - Xiong, Guoping; He, Pingge; Liu, Lei; Chen, Tengfei; Fisher, Timothy S.
Abstract : Ni–Co–Mn triple hydroxide (NCMTH) nanoneedles were coated on plasma-grown graphitic petals (GPs) by a facile one-step hydrothermal method for high-rate and long-cycle-life pseudocapacitive electrodes. Abstract : Ni–Co–Mn triple hydroxide (NCMTH) nanoneedles were coated on plasma-grown graphitic petals (GPs) by a facile one-step hydrothermal method for high-rate and long-cycle-life pseudocapacitive electrodes. Structural and compositional characteristics of NCMTHs indicate that the multi-component metal elements distribute homogeneously within the NCMTHs. Comparison of the electrochemical performance of the three-dimensional NCMTH electrodes to Ni–Co double hydroxides reveals that a synergistic effect of the hierarchical structure of GPs and NCMTHs enables their high rate capability and long cycle life. The NCMTH electrode maintains over 95% of its capacitance at a high charge/discharge rate of 100 mA cm −2 relative to its low-current (1 mA cm −2 ) capacitance; and it exhibits very high specific capacitance of approximately 1400 F g −1 (based on the mass of NCMTH), high specific energy density (≈30 W h kg −1 ) and power density (≈39 kW kg −1 ) at a high current density of 100 mA cm −2, and excellent long-term cyclic stability (full capacitance retention over 3000 cycles). To assess functional behavior, two-terminal asymmetric supercapacitor devices with NCMTHs on graphitic petals as positive electrodes were assembled and tested to reveal ultrafast charge/discharge rates up to 5000 mV s −1 (approx. two orders of magnitude faster than conventional asymmetric devices based on metal hydroxides) with high rate capabilities, and excellent long-term cyclic stability (full capacitance retention over 10 000 cycles).